Effectiveness of online integrative trans-diagnostic treatment on internet addiction and high-risk behaviors in female adolescents with borderline personality disorder with comorbid depressive disorder - Mohamadpour, Fahimeh; Mohammadi, Nurallah (Frontiers in Psychiatry, 2024)
Background Based on research, borderline personality disorder is associated with many behavioral and emotional problems, including Internet addiction and high-risk behaviors. On the other hand, integrative trans-diagnostic treatment, by targeting trans-diagnostic factors in emotional pathology, is considered a suitable treatment for comorbid psychological pathologies. Also, since in adolescence, the opinion of others about oneself is more important, online therapy has the advantage of protecting them from the fear of stigma and shame in the face of others’ judgments. Therefore, the aim of the current research was to investigate the effectiveness of online integrative trans-diagnostic treatment on the internet addiction and high-risk behaviors in adolescents with borderline personality disorder. Methods The current research was applied and quasi-experimental in a pre-test-post-test manner with a control group. The research sample included 40 female adolescents with borderline personality disorder who were randomly divided into two groups of 20 people, experimental and control groups. The criteria for entering the research included the age range of 12 to 18 years, female, confirmation of the disease by a psychologist, not receiving other psychological treatments in the last 3 months, and having a smartphone to participate in the online group. Substance abuse, any serious mental and physical illness/disorder that interferes with treatment, and failure to attend more than two sessions in therapy sessions were some of the exclusion criteria.The participants were tested on the scales of internet addiction and high-risk behaviors. Then, the treatment plan based on online integrative trans-diagnostic group therapy was presented to the participants of the experimental group online in 9 two-hour sessions. The control group was placed on the waiting list until the completion of the treatment sessions and the post-test implementation, and after the post-test implementation, they received the treatment. Then, their scores were measured, after completing the treatment, and a three-month follow-up period. Descriptive statistics and covariance test were used to analyze the data. Results Patients showed a clear improvement in the severity of internet addiction and high-risk behavior symptoms. So that the scores of internet addiction and high-risk behaviors in the experimental group after receiving the treatment, as well as after a three-month follow-up period, were significantly reduced (p < 0.001). Conclusion These results show that online integrative trans-diagnostic therapy can be an effective treatment option for reducing some symptoms of risky behaviors and internet addiction in adolescents with borderline personality disorder and should be studied further. It is noteworthy that the limitations of this study were the available sampling method, the use of a unisex sample of female patients, and the short-term follow-up period, which makes it difficult to generalize the results.